TINJAUAN FILOSOFIS TENTANG HIDUP, TUJUAN HIDUP, KEJAHATAN, TAKDIR, DAN PERJUANGAN - Palindangan, Linus K. (MAJALAH ILMIAH WIDYA, 2012)
Life and aspects related to life can be reviewed philosophically which is always interesting to discuss. Even thinkers havediscussed it at any time; saving the lives of a number of questions remain. The purpose of this paper is to provide an insight aboutlife philosophically. The approach used in this study is a research literature with the help of philosophy. It can be concluded that: (1)the life we have today evolved from the evolutionary process, (2) life in the process of evolution toward a goal, (3) there is evil inhuman life born from the creation of human limitations, (4) still the problem of destiny require further explanation, (5) the struggle ispart and parcel of human life.